Trade and Foreign Exchange Policies in Iran : Reform Agenda, Economic Implications and Impact on the Poor - World Bank (Washington, DC, 2013)
Iran's economic performance in the last two decades has been very disappointing. This is highlighted by the fact that per capita GDP was 16 percent lower in 1998 than in 1979. However, the most important single reason for this poor performance was not any domestic economic policy, but the long and costly war with Iraq. Fluctuations in oil prices and the US embargo also adversely affected the economy. Once the war with Iraq had finished, economic performance began to improve slowly; in the decede ending in 1998 per capita GDP growth was positive, although it averaged only 3 percent per year. Although less important than the war with Iraq, Iran's domestic economic policies have not been conducive to rapid economic growth. Economic performance has been and still is hampered by administered prices; large, poorly targeted subsidies; multiple exchange rates (Which remain important, despite recent progress in reducing disparities among them); trade restrictions; and state domination of economic activity. All banks in Iran are sdtate owned, and most large firms are owned by the state or by the quasi-public religious foundations. This report describes Iran;s trade and exchange rate policies, proposes and explains a reform program, and develops a computable general equilibrium of Iran's economy to estimate the gains--to the economy as a whole and to the poor--likely to accrue from various reform options. The report also recommends a program for sequencing the reforms.